2019
DOI: 10.1140/epjd/e2019-100067-4
|View full text |Cite
|
Sign up to set email alerts
|

Classification of head-on collisions of ion-acoustic solitary waves in a plasma consisting of cold ions and Boltzmann electrons

Abstract: Head-on collisions of ion-acoustic solitary waves in a collisionless plasma consisting of cold ions and Boltzmann electrons are studied using the particle-in-cell simulation. It is shown that the collision of solitary waves can occur under different scenarios. Solitary waves preserve or do not preserve their amplitudes and shapes after a collision, depending on their initial amplitudes. The range of initial amplitudes, at which a solitary wave preserves its identity after collisions, is established. The use of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Similarly, it can be seen from figure 2(d) that coupled Alfvén and ion-acoustic soliton amplitude is decreased while its width is increased with the increase in the wave propagation angle with respect to the external magnetic field. The negative value of comoving frame speed i.e., V=−0.01 means here that the speed of the coupled Alfvén and ion-acoustic cnoidal wave structure in the laboratory frame lies in the sub-Alfvénic region as it becomes less than the phase speed of the wave i.e., = + V V V l 0 which has been defined after equation (54). It is evident from figure 3(c) that the amplitude of the cnoidal wave structure is decreased, while its wavelength is enhanced with the increase in the plasma β value.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it can be seen from figure 2(d) that coupled Alfvén and ion-acoustic soliton amplitude is decreased while its width is increased with the increase in the wave propagation angle with respect to the external magnetic field. The negative value of comoving frame speed i.e., V=−0.01 means here that the speed of the coupled Alfvén and ion-acoustic cnoidal wave structure in the laboratory frame lies in the sub-Alfvénic region as it becomes less than the phase speed of the wave i.e., = + V V V l 0 which has been defined after equation (54). It is evident from figure 3(c) that the amplitude of the cnoidal wave structure is decreased, while its wavelength is enhanced with the increase in the plasma β value.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The experimental observations of ion-acoustic waves in a collisionless electron-ion plasma remain problematic despite the possibility of existence of plasma [54]. Experimental investigations in dusty plasmas demonstrated that the presence of negatively charged dust grains increases the phase velocity of the waves, and at the same time, also reduces the strength of the collisionless (Landau) damping to which the waves are subjected [55,56].…”
Section: Discussionmentioning
confidence: 99%